Formulação de substrato para produção de basidiocarpos de Pycnoporus sanguineus - Martinazzo-Portz, Tatiane (2011)
The biochemical composition of fungi can vary with climatic conditions and cultivation substrate. Several species have shown biochemical activities, such as Pycnoporus sanguineus, which is highlighted by orange to red color of their basidiocarps. Although the antimicrobial activity verified in various fields such as pharmaceutical, industrial and agricultural, there is no method for growing basidiocarps described in the literature. This work aimed to develop a substrate with Eucalyptus sp. for the cultivation of P. sanguineus and production of basidiocarps. There were two assays, and in vitro and in formulated substrate, developed in the Unioeste, Campus of Marechal Cândido Rondon. We used sawdust of Eucalyptus sp. Separate in two particle sizes: less than 500 microns (G1) and between 500 and 841 microns (G2). In the in vitro assay were used four isolates of P. sanguineus (Ps04, Ps08, PS13 and PS14), grown in Petri dishes containing culture medium CBA plus sawdust in the proportions of zero, 1, 5, 10 and 15% for both sizes. In each dish was peaked a 0.5 cm disc containing mycelium and kept in dark at 25±2ºC, until the first treatment to reach the edge of the Petri dish. Was evaluated the diameter of colony, growth rate of mycelium, the fresh weight of mycelium and production of the pigment cinnabarin. The experiment was DIC in 4x2x5 factorial design, four isolates of P. sanguineus, two particle size of sawdust of Eucalyptus sp. and five concentrations of sawdust added to the culture medium, both with six repetitions. In the assay with formulated substrate, we used two isolates of P. sanguineus (Ps08 and Ps14), grown in polypropylene bags of 28x16 cm, containing sawdust of Eucalyptus sp. and rice bran. At zero, 5 and 20%, particle size in G1 and G2, with humidity of 75% and compacted to 0.5 g mL-1. The substrates remained 30 days in BOD at 25±2ºC, then taken to the greenhouse. Two havest of basidiocarps were made, at 90 and 180 days. Where were evaluated diameter, fresh and dry weight, the average number of basidiocarps and production cinnabarin. Was used experimental DIC in 2x2x3 factorial design, with two isolates of P. sanguineus, two particle size of sawdust of Eucalyptus sp. and three concentrations of rice bran added to sawdust, both with six repetitions. Was observed that the sawdust of Eucalyptus sp. is suitable for substrate for the production of basidiocarps of P. sanguineus, which is G1 showed better results only in vitro assays, while on substrate, the two particle sizes showed good results for the production isolates of P. sanguineus. The Ps08, produced more mass of basidiocarps, while the Ps14 showed higher content of cinnabarin in the basidiocarps. It can be concluded that the genetic characteristics of the biological potential of the isolates of P. sanguineus are more related to productive results that the characteristics of substrates used in this research